Chapter 2: cerebrospinal fluid pressure in the pathogenesis of glaucoma - Jonas, Jost B.; Ritch, Robert; Panda-Jonas, Songhomitra (New Trends in Basic and Clinical Research of Glaucoma, 2015)
The optic nerve head forms the interface between the intraocular compartment and the retrobulbar compartment. The former is characterized by what we term intraocular pressure (IOP) and the latter by orbital cerebrospinal fluid pressure (CSFP). The trans-lamina cribrosa pressure difference (TLCPD) is defined as the difference between the pressures in the two compartments. Any change in one of them can be associated with a disturbance of homeostasis of the optic nerve head, such as papilledema or glaucomatous optic neuropathy. In particular, glaucomatous optic neuropathy may be due to either an elevated IOP and/or an abnormally low orbital CSFP, or due to a change in the time-dependent relationship between the pulse-synchronous changes in IOP and orbital CSFP. Based on the triangular relationships between IOP, CSFP, and blood pressure, glaucoma may be described as an imbalance between these three pressure parameters, eventually leading to an increased TLCPD. Because the retinal and choroidal venous blood drains through the CSFP space, elevated CSFP may be associated with dilated retinal veins, increased incidence of retinal vein occlusions, higher prevalence and severity of diabetic retinopathy, and thicker choroid.